Regulatory B and T cells in Helicobacter pylori infection - Reddiar, Dona (2018)
In the human gastric mucosa, an inflammatory response stimulated by H. pylori infection can lead to gastric cancer and peptic ulcer disease. Expression of the i1 active variant of Vacuolating Cytotoxin A (VacA) by the colonising bacterial strain has been identified as an independent risk factor for disease. VacA skews the adaptive immune response towards a regulatory phenotype to promote persistent H. pylori colonisation. In H. pylori-infected individuals, regulatory T cells (Tregs), which suppress inflammation through mechanisms including interleukin-10 (IL-10) production, are thought to play a role in protection against extra-gastric diseases such as multiple sclerosis and oesophageal cancer. IL-10 is an immunomodulatory cytokine which is expressed by several immune cell types including regulatory B cells (Bregs), whose role in H. pylori infection is unclear.